Zinc oxide for solar water splitting: A brief review of the material's challenges and associated opportunities. (December 2018) - Kegel, Jan; Povey, Ian M.; Pemble, Martyn E.
Abstract: In order to establish an energy system based on intermittent renewable energies it is of the highest importance to develop efficient and commercially viable technologies. In this regard, metal oxides are particularly promising materials to be used in core technologies such as photovoltaics or solar fuel production as well as in energy storage technologies such as batteries. In particular, the production of solar fuels by photo-(electro)chemical methods is currently considered to be the ' holy grail ' of energy research by some. This high consideration stems from the desirability of converting solar energy directly into chemical bonds and thus into a storable energy carrier. In this regard, the generation of hydrogen via solar water splitting forms a key building block related to this field of research. As a result of its low-cost, environmentally-friendly and earth-abundant nature, ZnO represents a promising material for this application. However, this material possesses some natural limitations, which are currently hindering the use of ZnO for solar water splitting. After considering some general material properties, this review introduces strategies that have been applied to increase the performance of ZnO for photo-(electro)chemical applications. It is discussed how these can help to overcome the most urgent material challenges, such as low visible-light absorption, fast charge carrier recombination and the deterioration of the material due to photo-corrosion. The focus of this short review is therefore on the opportunities associated with different synthetic approaches to manipulate the material's structure, defect-chemistry, opto-electronic properties and chemical stability. Thus nano-structuring, defect-engineering, doping and functional over-coating strategies are analyzed and their potential for the facilitation of ZnO's use for solar water splitting are outlined. Graphical abstract: A non-exhaustive literature review on the main limitations associated with the use of zinc oxide for solar water splitting and how to overcome them by using structural- and defect-engineering, doping and over-coating with functional layers. Highlights: The major natural limitations that hinder the use of zinc oxide for solar water splitting are summarized. Important literature reports are reviewed that present synthetic approaches to overcome these limitations. Structural- and defect-engineering, doping as well as the over-coating of zinc oxide with functional layers are discussed as strategies to overcome the material's challenges.